A method for preparing "brick-mud" isomorphous metal materials by electroforming
By adopting a linear anode scanning electroforming system in electroforming technology, the voltage between the electrodes and scanning speed is regulated, the "brick-mud" structure is introduced on elemental metals, which solves the problem that the existing technology is difficult to improve material performance, and obtains a high-performance and extremely high-purity "brick-mud" structural metal material.
Patent Information
- Application Number
- CN202210894435.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-07-28
Smart Images

Figure CN115198317B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electroforming, and in particular relates to a method for preparing "brick-mud"-like isomorphous metal materials by electroforming. Background Art
[0002] Strength and toughness are two basic indicators for evaluating the advancement of metal structural materials, but there is often a trade-off between the two. Therefore, how to achieve a perfect match between the two has always been one of the research hotspots in the field of materials. Since the microstructure of a material determines its macroscopic mechanical properties, metal materials with different performance units at the microscale, that is, by constructing different "soft" and "hard" parts in the material, the soft phase provides toughness and the hard phase provides strength, the performance of the material can be improved, such as gradient structure, "brick-mud" structure, etc. Gradient material refers to a material whose grain size changes in a gradient in one direction. "Brick-mud" structure refers to the alternating stacking of "bricks" (hard phase materials) and "mud" (soft phase materials). "Bricks" are the main carrier of material strength, and "mud" bears large elastic deformation and disperses mechanical energy. Therefore, if such a structure is introduced into the material, the performance of the material can be improved.
[0003] Electroforming is an additive precision manufacturing technology. It is based on the principle of metal ion electrodeposition. After a certain thickness of metal, alloy or metal-based composite material is deposited on the cathode surface, it is separated from the cathode by certain technical means. In the preparation of metal materials, electroforming has unique advantages. By changing the solution composition and working conditions, the performance of the electroformed layer can be changed in a wide range, and the prepared metal material is of high purity. At present, the change of grain size in the electroforming process is mainly achieved by applying additives, using pulse power supply or changing the current waveform. For example, Qin et al. prepared a nickel coating with a grain size ranging from 586nm to about 22nm from the substrate to the surface by gradually changing the concentration of the grain refiner (saccharin) during direct current electrodeposition (Qin L, Xu J, Lian J, et al. A novel electrodeposited nanostructured Nicoating with grain size gradient distribution[J]. Surface and Coatings Technology, 2008, 203(1-2): 142-147.). Chinese patent CN113388871A proposes a gradient material that achieves a gradient change in grain size along the surface direction by changing the current waveform. However, these two methods have certain limitations. Either they need to use a grain refiner, which will introduce foreign impurities and reduce the purity of the material, or they need to use a pulse power supply or a modulated power supply, which is inconvenient to operate and has high cost. On the other hand, it is difficult to prepare materials with gradients in two directions. The "brick-mud" structure can achieve changes in the microstructure of the material in two directions, but currently this "brick-mud" structure is mostly used to design and manufacture composite materials, such as Chinese patents CN 114058920A, CN111136999A, CN108959786A, etc. There are few theoretical and technical research reports on the application of this "brick-mud" structure to single-element materials.
[0004] Therefore, the present invention proposes a method for preparing a "brick-mud" structure of a single-element heterogeneous metal material by electroforming, and introduces a "brick-mud" structure on a single-element metal to improve the performance of the material. Fine grains at the nanoscale with high hardness and high strength are used as "bricks", and coarse grains at the micron level and above with high toughness are used as "mud". The two are combined to form a "brick-mud" structure, thereby realizing changes in the microstructure of the material in the thickness direction (normal direction) and in the direction parallel to the surface of the material. The present invention is based on a line anode scanning electroforming system, using a linear inert anode and a small inter-electrode gap, so that the voltage / current between the cathode and the anode will act on a very narrow band area on the cathode surface, and the current density on the cathode surface during the line anode scanning electroforming process approximately obeys a Gaussian distribution. Based on the Butler-Volmer equation, the overpotential at the cathode also has similar distribution characteristics. According to the electrocrystallization theory in electrochemical principles (see the formula below), the higher the cathode overpotential, the easier it is for the crystal nucleus to form, the faster the crystal nucleus formation rate, the more crystal nuclei there are, and the more finely crystalline the deposited layer is. On the contrary, the smaller the cathode overpotential, the coarser the grains of the deposited layer. Moreover, research (Xiao Y, Ming P, Zhang X, et al. Ultrahigh strengthultrapure nanostructured nickel metal prepared via ultrafine anode scanningelectrodeposition[J]. Materials & Design, 2022, 213: 110339.) shows that under the same inter-electrode voltage, the greater the scanning speed of the line anode, the higher the cathode overpotential.
[0005]
[0006] Where, ω represents the nucleation rate; K represents the prefactor; h is one atom high; σ is the interfacial tension of the nucleus / solution; L is the Avogadro constant; A is the atomic weight of the deposited metal; ρ is the density of the deposited metal; n is the valence of the metal ion; F is the Faraday constant; R is the gas constant; T represents the temperature; η c is the cathode overpotential.
[0007] Therefore, in the process of online anode scanning electroforming, the magnitude of the overpotential is affected by both the scanning motion speed and the current density. If the scanning speed and the inter-electrode voltage can be regularly and cooperatively regulated, the magnitude and distribution of the overpotential on the cathode surface will also change periodically accordingly, resulting in a corresponding change in the distribution of the electrodeposited metal grains. During operation, the line anode structure is constantly reciprocating, and the current received by each conductive area on the cathode surface is localized and transient, and the metal is thickened in a layered manner on the cathode surface. Based on this principle, the present invention proposes a method for electroforming a "brick-mud" structured single-element heterogeneous metal material by simultaneously and regularly changing the inter-electrode voltage and the scanning speed along the scanning motion direction and the thickness direction, so as to prepare a "brick-mud" structured single-element heterogeneous metal material with alternating coarse grain layers and fine grain layers of hundreds of microns and tens of nanometers in thickness and in two directions parallel to the material surface. Summary of the invention
[0008] The present invention provides a method for preparing a "brick-mud"-like isomorphous metal material by electroforming, thereby realizing simple preparation of the material.
[0009] To achieve the above object, the technical solution of the present invention is as follows.
[0010] A method for preparing a "brick-mud" isomeric metal material by electroforming, comprising the following steps:
[0011] S1: Install and debug the line anode scanning electroforming system, embed the anode into the stirring paddle, and expose the anode with a width of no more than 50μm, so that the two form an integral line anode structure, removably install the cathode substrate horizontally in the electroforming tank, place the line anode structure directly above the cathode substrate and make its lower surface parallel to the upper surface of the cathode substrate and separated by a constant gap, electrically connect the positive and negative electrodes of the electroforming power supply to the line anode structure and cathode substrate of the electroforming system respectively, move the line anode structure to the edge of the cathode substrate, and then inject electrolyte into the electroforming tank until the liquid level is 5-10mm higher than the lower surface of the line anode structure, and maintain this liquid level unchanged under the action of the electrolyte circulation filtration system;
[0012] S2: Drive the line anode structure to perform a linear scanning motion from the starting position set on the cathode substrate, and adjust the scanning speed through the speed controller, so that the line anode structure alternately runs the strokes of L1 and L2 in a slow-fast manner until the line anode structure moves to the end position set on the cathode substrate, and then returns to the starting point in the same displacement and speed matching manner, thereby completing a periodic scanning motion. At the same time, a low voltage U is applied to the line anode structure and the cathode substrate respectively under the slow and fast scanning motions. 低 and high voltage U 高In this way, under the combined action of the electric field and the electrolyte, a metal layer will be electrodeposited on the surface of the cathode substrate, forming a nanocrystalline metal layer with a grain size of nanometers at a fast scanning speed and high voltage, and a coarse-crystalline metal layer with a grain size of micrometers and above at a slow scanning speed and low voltage. When the thickness of the deposited layer reaches the set value, the scanning motion is stopped and the electroforming power supply is turned off, and the line anode structure is adjusted to the starting position;
[0013] S3: The speed controller is used to change the scanning speed, so that the line anode structure alternately runs the strokes L1 and L2 in a fast-slow manner until the line anode structure moves to the end position set on the cathode substrate, and then returns to the starting point in the same displacement and speed matching manner, thereby completing a periodic scanning movement. During the movement, the line anode structure is operated at a high speed and high voltage U 高 Matching, slow speed and low voltage U 低 In a coordinated manner, the line anode structure and the cathode substrate are powered, and the line anode structure is continuously driven to perform reciprocating scanning motion until the metal layer thickens to a set value, and then the scanning motion is stopped and the electroforming power supply is turned off, and the line anode structure is adjusted to the starting position;
[0014] S4: Repeat steps S2 and S3 in sequence until the total thickness of the electroformed metal material reaches the set value. At this time, turn off the electroforming power supply, stop the scanning movement, adjust the line anode structure to the starting position, shut down the electrolyte filtration circulation system, take out the metal material for cleaning, drying and separation from the cathode substrate, and obtain a "brick-mud"-like isomorphous heterogeneous metal material with coarse-grained metal layers and fine-grained metal layers alternately stacked in the thickness direction (normal direction) and in the direction parallel to the material surface.
[0015] The fast speed is 40mm / s-80mm / s, and the slow speed is 0.5mm / s-2mm / s.
[0016] The voltage U 高 is the voltage U 低 2-5 times of.
[0017] The gap between the lower surface of the linear anode structure and the upper surface of the cathode substrate is no greater than 500 μm.
[0018] The anode of the line anode scanning electroforming system is made of an electrochemically inert conductive metal material.
[0019] The stirring paddle of the line anode scanning electroforming system is made of an electrical insulating material resistant to acid and alkali corrosion.
[0020] Compared with the prior art, the present invention has the following main advantages:
[0021] (1) A single-element heterogeneous "brick-mud" structure metal material with a large grain size span and extremely high purity can be obtained. Because the technical solution of the present invention uses physical parameters such as inter-electrode voltage and scanning speed to control the grain size, it can achieve the preparation of extremely fine grains and coarse grains, so that the difference between the "brick structure" layer (corresponding to extremely fine grains) and the "mud structure" layer (corresponding to coarse grains) is obvious. Other existing methods, such as pulse power supply + addition of organic additives or addition of alloy elements, cannot achieve this. In addition, since the present invention does not add organic additives and other alloy elements, it avoids the introduction of heterogeneous components, minimizes the weakening of material properties caused by the introduction of impurities, and makes the prepared material extremely pure; (2) It is easy to implement and simple to operate. The electroforming of single-element heterogeneous "brick-mud" structure metal materials based on the technical solution of the present invention can be completed in the same electroforming tank, and the electrolyte composition used is simple, and a conventional DC power supply can be used, without additives and complexing agents, and without pulse power supplies or other types of modulated power supplies. It is only necessary to coordinately adjust the scanning speed of the line anode structure and the inter-electrode voltage and other physical parameters within the set scanning stroke. The preparation method is simple, easy to operate, and easy to control.
[0022] (3) Easy to regulate material structure and performance. The patented technical solution of the present invention can obtain homogeneous and heterogeneous materials with varying grain size, specific grain size distribution range and thickness by simply adjusting the speed of the scanning movement of the linear anode structure within a set stroke (the stroke can also be changed as needed) and adding the inter-electrode voltage matched therewith, thereby obtaining a metal material with variable microstructure and performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the line anode scanning electroplating system.
[0024] Figure 2 Schematic diagram of a "brick-mud"-like isomorphous metal material prepared by the present invention.
[0025] Figure 3 Velocity, displacement, and voltage matching diagram for the slow-fast alternating layer.
[0026] Figure 4 Velocity, displacement, and voltage matching diagram for the fast-slow alternating layers.
[0027] Numbers and names in the figure: 1. Speed controller; 2. Electroforming power supply; 3. Stirring paddle; 4. Anode; 5. Coarse-grained metal layer; 6. Nanocrystalline metal layer; 7. Cathode substrate; 8. Filtration circulation system; 9. Electrolyte; 10. Electroforming tank; 11. Wire anode structure. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the contents described above.
[0029] like Figure 1 As shown, a line anode scanning electroforming system uses a platinum sheet with a purity of 99.99% as the anode 4, whose length, width and thickness are 100mm, 10mm and 50μm respectively, and is embedded in the stirring paddle 3, exposing a linear area with a length of 100mm and a width of 50μm, so that the two constitute a line anode structure 11. The stirring paddle 3 is made of organic glass. The material of the cathode substrate 7 is 304 stainless steel, and its length, width and thickness are 210mm, 210mm and 1mm respectively. Except for the upper surface, the remaining surfaces are all insulated. After the upper surface is polished, it is then subjected to alkaline washing, oil removal and acid washing activation treatment, and finally rinsed with deionized water and dried for use. The electrolyte 9 is composed of 450g / L of nickel sulfamate and 10g / L of boric acid. The pH of the electrolyte is 3.8 and the temperature is maintained at about 50°C.
[0030] After installing and debugging the line anode scanning electroforming system, the cathode substrate 7 is detachably installed horizontally in the electroforming tank 10, the line anode structure 11 is placed directly above the cathode substrate 7 and its lower surface is parallel to the upper surface of the cathode substrate 7 and is 400 μm apart, the positive and negative electrodes of the electroforming power supply 2 are electrically connected to the line anode 11 and the cathode substrate 7 of the electroforming system respectively, the line anode structure 11 is moved to the edge of the cathode substrate 7, and finally the electrolyte 9 is injected into the electroforming tank 10 until the liquid level is 10 mm higher than the lower surface of the stirring paddle 3, and this liquid level is maintained unchanged under the action of the electrolyte circulation filtration system 8.
[0031] The speed controller 1 is used to control the scanning speed so that it follows Figure 3 The speed and displacement matching method shown in the figure starts the movement, the slow speed is set to 1mm / s, the fast speed is set to 40mm / s, the movement strokes L1 and L2 at the two speeds are 10mm and 40mm respectively, and the single direction movement stroke is 210mm. At a speed of 1mm / s, a low voltage U is applied to the line anode structure 11 and the cathode substrate 7. 低 Set to 3V, high voltage U at 40mm / s 高Set to 9V, drive the line anode structure 11 to perform a linear scanning motion from the starting position set by the cathode substrate 7 until the line anode structure 11 moves to the end position set on the cathode substrate 7, and then returns to the starting point at the same speed, displacement and voltage matching method, thereby completing a cycle scanning motion. At this time, a metal layer is electrodeposited on the surface of the cathode substrate 7 under the combined action of the electric field and the electrolyte, and a nanocrystalline metal with a grain size of nanometers is formed under a fast scanning speed and high voltage, and a coarse-grained metal with a grain size of micrometers and above is electrodeposited under a slow scanning speed and low voltage. The line anode structure 11 is continuously driven to perform a reciprocating scanning motion until the metal layer thickens to 8μm, turn off the electroforming power supply 2 and stop the scanning motion, and then adjust the line anode structure 11 to the starting position.
[0032] The speed controller 1 is used to control the scanning speed so that it follows Figure 4 The speed and displacement matching mode shown in the figure starts the movement, the fast speed is set to 60mm / s, the slow speed is set to 2mm / s, the movement strokes L1 and L2 at the two speeds are 10mm and 40mm respectively, and the single direction movement stroke is 210mm. At a speed of 60mm / s, a high voltage U is applied to the line anode structure 11 and the cathode substrate 7. 高 Set to 10V, low voltage U at 2mm / s 低 is 4 V, driving the line anode structure 11 to do a straight line scanning motion from the starting position set on the cathode substrate 7 until the line anode structure 11 moves to the end position set on the cathode substrate 7, and then returns to the starting point at the same speed, displacement and voltage matching method, and continuously drives the line anode structure 11 to do a reciprocating scanning motion until the metal layer thickens to 8 μm, turns off the electroforming power supply 2 and stops the scanning motion, and then adjusts the line anode structure 11 to the starting position.
[0033] The above electroforming steps are repeated in sequence until the total thickness of the electroformed metal material reaches 32 μm. At this time, the electroforming power supply 2 is turned off, the scanning motion is stopped, and the line anode structure 11 is adjusted to the starting position. The electrolyte filtration circulation system 8 is turned off, and the metal material is taken out for cleaning, drying and separation from the cathode substrate 7. A "brick-mud"-like isomorphous metal material can be obtained in which coarse-grained metal layers and fine-grained metal layers are alternately stacked in the thickness direction (normal direction) and in the direction parallel to the material surface.
Claims
1. A method for preparing a "brick-mud" isomeric metal material by electroforming, characterized in that: It involves implementing the following steps in order: S1: Install and debug the line anode scanning electroforming system, embed the anode (4) into the stirring paddle (3), and expose the anode (4) with a width of no more than 50 μm, so that the two form an integral line anode structure (11), removably install the cathode substrate (7) horizontally in the electroforming tank (10), place the line anode structure (11) directly above the cathode substrate (7) and make its lower surface parallel to the upper surface of the cathode substrate (7) and separated by a constant gap, electrically connect the positive and negative electrodes of the electroforming power supply (2) to the line anode structure (11) and the cathode substrate (7) of the electroforming system respectively, move the line anode structure (11) to the edge of the cathode substrate (7), and then inject electrolyte (9) into the electroforming tank (10) until the liquid level is 5-10 mm higher than the lower surface of the line anode structure (11), and maintain this liquid level unchanged under the action of the electrolyte filtration circulation system (8); S2: driving the line anode structure (11) to perform a linear scanning motion from the starting position set on the cathode substrate (7), and regulating the speed of the scanning motion through a speed controller (1), so that the line anode structure (11) alternately runs in a slow speed-fast speed manner for a stroke of L1 and L2 respectively, until the line anode structure (11) moves to the end position set on the cathode substrate (7), and then returns to the starting point in the same displacement and speed matching manner, thereby completing a cycle scanning motion. At the same time, voltages U are applied to the line anode structure (11) and the cathode substrate (7) respectively under the slow speed and fast speed scanning motions. 低 and voltage U 高 Thus, under the combined action of the electric field and the electrolyte (9), a metal layer is electrodeposited on the surface of the cathode substrate (7) at a fast speed and voltage U 高 A nanocrystalline metal layer (6) with a grain size of nanometers is formed at a slow speed and a voltage U 低 Electrodepositing a coarse-grained metal layer (5) having a grain size of micrometers or above, when the thickness of the deposited layer reaches a set value, stopping the scanning movement and turning off the electroforming power supply (2), and adjusting the line anode structure (11) to the starting position; S3: The speed of the scanning movement is changed by the speed controller (1), so that the line anode structure (11) alternately runs the strokes L1 and L2 respectively in a fast speed-slow speed manner, until the line anode structure (11) moves to the end position set on the cathode substrate (7), and then returns to the starting point in the same displacement and speed matching manner, thereby completing a periodic scanning movement. During the movement, according to the fast speed and voltage U 高 Coordination, slow speed and voltage U 低 In a coordinated manner, the line anode structure (11) and the cathode substrate (7) are powered, and the line anode structure (11) is continuously driven to perform a reciprocating scanning motion until the metal layer thickens to a set value, and then the scanning motion is stopped and the electroforming power supply (2) is turned off, and the line anode structure (11) is adjusted to a starting position; S4: Steps S2 and S3 are repeated in sequence until the total thickness of the electroformed metal material reaches a set value. At this time, the electroforming power supply (2) is turned off, the scanning motion is stopped, and the line anode structure (11) is adjusted to the starting position. The electrolyte filtration circulation system (8) is turned off, and the metal material is taken out for cleaning, drying and separation from the cathode substrate (7). Thus, a "brick-mud"-like isomorphous metal material with coarse-grained metal layers and fine-grained metal layers alternately stacked in both the thickness direction (normal direction) and the scanning direction (in the direction parallel to the material surface) can be obtained; The fast speed is 40mm / s-80mm / s, and the slow speed is 0.5mm / s-2mm / s; The voltage U 高 is the voltage U 低 2-5 times of.
2. The method for preparing a "brick-mud" isomeric metal material by electroforming according to claim 1, characterized in that: The gap between the lower surface of the linear anode structure (11) and the upper surface of the cathode substrate (7) is no greater than 500 μm.
3. The method for preparing a "brick-mud" isomeric metal material by electroforming according to claim 1, characterized in that: The anode (4) of the line anode scanning electroforming system is made of an electrochemically inert conductive metal material.
4. The method for preparing a "brick-mud" isomeric metal material by electroforming according to claim 1, characterized in that: The stirring paddle (3) of the line anode scanning electroforming system is made of an electrical insulating material resistant to acid and alkali corrosion.
Citation Information
Patent Citations
Method for preparing microstructure gradient change material based on current waveform modulation electroforming
CN113388871A